The downregulation of the miniature gene does not replicate miniature loss-of-function phenotypes in Drosophila melanogaster wing to the full extent - Bilousov, O.O.; Katanaev, V.L.; Kozeretska, I.A. (Цитология и генетика, 2013)
During maturation Drosophila wing epithelial cells undergo number of changes due to processes, which take place in the wing of the newly emerged fly, among which epithelialtomesenchymal transition (EMT) and apoptosis are pivotal. It is considered that neurohormone bursicon is responsible for their triggering. In turn, extracellular matrix protein Miniature is also essential for proper progress of apoptosis and, presumably, EMT. In accordance with our previously proposed hypothesis, Miniature and bursicon form stabilizing/accumulative complexes, which are able to diffuse freely within Drosophila wing, in such a way constitutively promoting enough concentrations of the maturation triggering signal. Here we tried to come to confirmation of our hypothesis from the other side, using UAS/GAL4 system and RNAisilencing techniques. Клетки эпителия крыла дрозофилы во время матурации претерпевают ряд изменений как следствие происходящих в это время в крыле мухи процессов, ключевыми из которых являются эпителиально-мезенхимальный переход (ЭМП) и апоптоз. Считается, что нейрогормон бурсикон ответствен за их запуск. В свою очередь белок внеклеточного матрикса Miniature также необходим для успешного прохождения апоптоза и, вероятно, ЭМП. Согласно предложенной нами ранее гипотезе Miniature и бурсикон формируют стабилизирующие/накопительные комплексы, которые способны свободно диффундировать в плоскости крыла, постоянно поддерживая тем самым достаточную для запуска процессов матурации концентрацию сигнала. Під час матурації клітини епітелію крила дрозофіли зазнають ряд змін за рахунок процесів, які відбуваються в цей час в крилі мухи, ключовими з яких є епітеліально-мезенхімальний перехід (ЕМП) та апоптоз. Вважається, що нейрогормон бурсикон відповідальний за їхній запуск. В свою чергу білок позаклітинного матриксу Miniature також є необхідним для успішного проходження апоптозу і, ймовірно, ЕМП. Відповідно до запропонованої нами раніше гіпотези Miniature та бурсикон формують стабілізуючі/накопичувальні комплекси, які здатні вільно дифундувати в площі крила, постійно підтримуючи тим самим достатню для запуску процесів матурації концентрацію сигналу.